2017
DOI: 10.1007/s10661-017-6203-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of trace metal concentrations in raw cow’s milk from three dairy farms in North Gondar, Ethiopia: chemometric approach

Abstract: Concentrations of essential (Cu, Mn, and Zn) and toxic (Cr, Cd, and Pb) trace metals in 30 raw cow's milk samples were quantified using flame atomic absorption spectrometry. The samples were collected from the Nara-Awudarda, Tana-Abo, and Kosoye Amba-Rass sites in North Gondar, Ethiopia, preserved in a deep freezer (-20 °C), and then digested by Kjeldahl apparatus with HNO/HO (5:2; v/v) at 300 °C for 2.5 h. The data were subject to principal component analysis (PCA) and partial least square-discriminant analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 33 publications
0
15
1
Order By: Relevance
“…Results presented in Table 4 and 5 show that, the average Cr concentration, in cow's milk analyzed ranged from 0.00 -0.4 ppm which is lower than 0.845 -0.895 and 0.468-0.828 ppm reported by Belete et al (2014) and Akele et al (2017) in Ethiopia respectively and higher than 0.055 -0.075 and 0.0 -0.11 ppm reported by Alem et al (2015) in Ethiopia and Ahmad et al (2016) in Bangladesh respectively. Only sample CM13 one exceeded the permissible limit.…”
Section: Resultsmentioning
confidence: 59%
“…Results presented in Table 4 and 5 show that, the average Cr concentration, in cow's milk analyzed ranged from 0.00 -0.4 ppm which is lower than 0.845 -0.895 and 0.468-0.828 ppm reported by Belete et al (2014) and Akele et al (2017) in Ethiopia respectively and higher than 0.055 -0.075 and 0.0 -0.11 ppm reported by Alem et al (2015) in Ethiopia and Ahmad et al (2016) in Bangladesh respectively. Only sample CM13 one exceeded the permissible limit.…”
Section: Resultsmentioning
confidence: 59%
“…1-3). Another study of trace metal concentrations in Ethiopia by Akele et al (2017) reported that the range of Cu (0.8-1.532 µg .g -1 ), Pb (0.120-0.186 µg .g -1 )and Cd (0.244-0.330). In the present study, the range of Fe levels in buffalo's milk was found to be less than cow's milk (see fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some studies are in agreement with those reported in the literature from other countries. In their papers that the levels of Fe, Cu, Pb, Cd and Ni in cow and buffalo's milk and their products were unsafe for consumers (Licata et al, 2012;Malhat et al, 2012;Temiz & Soylu, 2012;Tona et al, 2013;El-Ansary & El-Leboudy, 2015;Ojezele et al, 2017), while others have reported no significant effect cause any adverse health concerns to consumers (Najarnezhad & Akbarabadi, 2013;Belete et al, 2014;Cadar et al, 2015;Najarnezhad et al, 2015;Perez-Carrera et al, 2016;Ahmad et al, 2017;Akele et al, 2017). More reviews providing in-depth discussions can be found in recent papers (Noori et al, 2016;Ziarati et al, 2018).…”
Section: Creammentioning
confidence: 99%
See 1 more Smart Citation
“…The research done by Akele et al [59] reported heavy metal concentrations in milk samples in the following decreasing order: Zn > Mn> Cu > Cr > Cd > Pb in Chilga and Dembia and Mn> Zn > Cu > Cr in Wogera milk samples. The highest concentration in milk samples is probably due to high mineral enrichment and metal leaching (especially Cd and Pb) from coal deposits cross contamination in the chain.…”
Section: Heavy Metalsmentioning
confidence: 97%